Characteristics, management, and outcomes of patients with follicular dendritic cell sarcoma. (6th April 2017) - Jain, Preetesh; Milgrom, Sarah A.; Patel, Keyur P.; Nastoupil, Loretta; Fayad, Luis; Wang, Michael; Pinnix, Chelsea C.; Dabaja, Bouthaina S.; Smith, Grace L.; Yu, Jun; Hu, Shimin; Bueso Ramos, Carlos E.; et al.
Summary: Dendritic cell sarcomas are rare tumours of antigen presenting cells. Data regarding their biology, management and outcomes are sparse. We analysed 66 patients with follicular dendritic cell sarcoma (FDCS). Six patients also had Castleman disease, 9 had another malignancy and 13 had an autoimmune disease. Fifty‐four per cent of patients presented with localized disease and 46% with systemic involvement. The median progression‐free (PFS) and overall survival (OS) following frontline therapy was 21 and 50 months, respectively. Survival outcomes were significantly inferior in patients with extranodal, bulky or intra‐abdominal disease at presentation. Stage was not associated with survival. Management approaches were heterogeneous. Patients who underwent an upfront gross total resection (GTR) experienced better PFS and OS (both P  < 0·0001). In patients who underwent a GTR, consolidative radiotherapy was associated with improved local control ( P  = 0·03), PFS ( P  = 0·04) and OS ( P  = 0·05). In patients with measureable disease, gemcitabine with a taxane yielded an overall response rate of 80%. The pattern of relapse was predominantly locoregional. Salvage rates after recurrence were poor. Studies are underway at our institution to define the genomic profile in FDCS and identify potential novel therapeutic targets.